Effects of biochar and nitrogen fertilizer on soil physicochemical properties, nitrogen use efficiency and upland rice (Oryza sativa) yield grown on an Alfisol in Southwestern Nigeria - Segun Oladele; Adebayo Adeyemo; Moses Awodun; Ayodele Ajayi; Abayomi Fasina (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Biochar and inorganic fertilizer when co-applied have been reported to increase crop yield and enhance soil fertility. However, studies on this complementary effect on soil properties and rain-fed upland rice performance in Sub-Saharan Africa are still scanty.